نمط جديد لتقدير عدة أيونات باستعمال فوتوميتر محمي معتمدا عمى استعمال ثنائي وصمة باعث ومتحسسات فوتوسميكونية متعددة - خليل علي إبراهيم; عبد الستار هاشم جبار; شاكر عصام محمد علي (Al-Nahrain Journal of Science, 2011)
This research article presents a spectral system – home made for the determination of some selected ions. e:g. Mn(II), PO43-, Fe(III), NO2- and NO3- using the conventional spectrophotometric determination. Mn(II) was determined by its oxidation with KIO4 in an acidic medium to violet MnO4- using the green LED.(Light Emitting Diode) While PO43- was determined using ammonium molybdate and ascorbic acid which is used as a reducing reagent. To form the blue molybdenum using the red LED. While iron (II) was determined as 1,10-phenathroline using the blue LED. Nitrite was determined using gress method using the orange LED. While nitrate ion was first reduced then determined by gress method. The home made instrument was well compared with a standard commercial LKB instrument at 525, 630, 485, and 600 nm for Mn(II), PO43-, Fe(II), NO2- & NO3- successively. Linear calibration of 110-4 – 30 ppm for Mn(II), 510-4 – 13 ppm for PO43-, 810-3-4.5 ppm for Fe(II), 510-4-7 ppm for NO2- and 510-4-9 ppm for NO3- with a correlation coefficient of 0.9998, 0.9950, 0.9995, 0.9987, 0.9989 for each successive ion. Also a detection limit of 1.4310-5, 5.110-3, 2.3110-4 and 3.4910-5 ppm successively. All these were done with the home made instrument. While using the LKB instrument the linear calibration graphs were 0.01-30, 0.01-16, 0.01-3.5, 0.0510-2-4.0, and 0.0510-1-4.5 ppm with L.O.D of 0.0275, 0.0167, 0.0150, 0.0058 and 0.00929 ppm successively.The R.S.D% was <1% for n=13. using t-test, F-test proves that the new home made instrument can be used as an alternative instrument with good confidence.